Relationship between screen time, sleep duration, parent-child interaction and psychosocial adjustment among preschool children in Selangor, Malaysia - Foo, Ning (2023)
The current study aimed to determine the relationship between screen time, sleep duration, parent-child interaction and psychosocial adjustment among preschool children in Selangor, Malaysia. The study also intended to determine whether a difference exists in psychosocial adjustment between males and females. Moreover, the study aimed to examine whether sleep duration and parent-child interaction mediate the relationship between screen time and psychosocial adjustment as well as explore unique predictors of psychosocial adjustment. A multistage cluster sampling method was employed to select the sample in this study. The sample consisted of 392 parents (either mother or father) of preschool children aged between four to six years old in Selangor. The Screen Time Questionnaire (STQ) was applied to measure screen time while the Children’s Sleep Habits Questionnaire (CSHQ) was used to measure sleep duration. Besides, the Parent-Child Interaction Checklist and the Strengths and Difficulties Questionnaire (SDQ) were utilized to assess parent-child interaction and psychosocial adjustment respectively. The relationship between screen time, sleep duration, parent-child interaction, and psychosocial adjustment was analysed using Pearson’s correlation analysis. Independent samples t-test was used to determine the difference in psychosocial adjustment between boys and girls. Multiple regression analysis was used to determine the unique predictors of psychosocial adjustment. Findings indicated that there was a significant difference in psychosocial adjustment (hyperactivity, peer problems, prosocial behaviour, and total difficulties) between boys and girls. Besides, there was a significant correlation between screen time and parentchild interaction. The child’s gender, father’s years of education, child calming screen time, and parent-child interaction were significant predictors of psychosocial adjustment. However, mediation analysis was unable to be conducted to determine the mediating role of sleep duration and parent-child interaction on the relationship between screen time and psychosocial adjustment, as screen time did not significantly correlated with psychosocial adjustment overall. This study provides a deeper understanding of how screen time, sleep duration, and parent-child interaction influence children’s psychosocial adjustment. It also provides a platform for future research to explore other factors that may influence children’s psychosocial adjustment.